Maternal and filial consumption of probiotics protects from acute stress-induced anxiety and loss of benevolent gut microbes: Probiotics protect from anxiety - Wali, Abdulazeez Kadhim; Mohajerani, Hamid Reza; Amini, Kumarss (Cellular and Molecular Biology, 2024)
The study aimed to determine the effects of probiotic consumption during pregnancy and lactation and post-weaning on acute stress-induced anxiety and gut beneficial microbiota of the female offspring mice.The female offspring mice were divided into several groups: intact, control (only stressed), PBS/dam (dams gavaged with PBS), PRO/dam (dams gavaged with probiotics), PRO/dam+off (both dams and offspring gavaged with probiotics), and PBS/dam+off (both dams and offspring gavaged with PBS)The probiotics chosen are mainly L. rhamnosus, B.breve, and B. longum (108 CFU/ml). Foot shock stress will be applied for one hour on the 43rd day after birth. Behavioral tests were conducted using the open field and elevated plus-maze. Corticosterone was measured by ELISA kit, and intestinal microflora with qPCR.The data showed that PRO/dam+off had more entries into open arms compared to the control group and decreased move distance and time spent in closed arms compared to the control group. However, there was no significant difference between the PRO/dam group and the control group. In the open field test, the control group spent less time in the inner zone compared to the intact group and in PRO/dam+off group. Corticosterone hormone was increased in the control group and was decreased in the PRO/dam+off. Bifidobacteria and Lactobacilli decreased in the control group in comparison to the intact group, and in the PRO/dam+off group increased compared with other groups. Maternal and filial supplementation with a multi-strain probiotic mixture increased levels of beneficial bacteria and reduced stress-induced anxiety in mice.